A Comparative Content Analysis of Pre-Internet and Contemporary Child Sexual Abuse Material. Issue 9 (2nd September 2022) - Salter, Michael; Whitten, Tyson
ABSTRACT: Child sexual abuse material is now recognized as a major social problem, however prior to the internet, disclosures of victimization in abuse material were the subject of skeptical scholarly commentary. The veracity of this skeptical position has been subject to limited empirical scrutiny. The aim of this study is to analyze the content of a sample of 1004 images of pre-internet abuse material. The pre-internet sample was analyzed according to the characteristics of victim/s, perpetrator/s and severity and setting of abuse, which were then compared to a preexisting dataset of 34, 561 contemporary abuse images. The findings of the study underscore the severity of pre-internet abuse material. The comparison between the pre-internet and contemporary sample found that the average age of girls abused in abuse material has decreased, and the severity of the material has increased. The study highlights the significant abuse experienced by abuse material victims prior to the internet, and suggests the popularization of the internet is linked to a trend toward more serious offending against children in abuse material. The consistent role of the home as the major site of abuse material production poses significant challenges to prevention, early intervention, and prosecution.